Growth and characterizations zinc tin oxide nanowire for nanoelectronic applications - Kuah, Wee Hian. (2010)
In the last 20 years of science and materials technology evolution, miniaturization has emerged as one of the most sought-after technology advancement. Since the first successful demonstration of metal oxide nanowires in high performance electronics, it has marked a new milestone for simple and flexible printed electronics. This project aims to investigate the growth of zinc tin oxide nanowires by vapour-liquid-solid method (VLS) and its application in electronic devices. Zinc tin oxide nanowires was grown from ZnO and SnO2 powders with molar ratio of 2:1 and at a temperature of 900°C through chemical vapour deposition. The molar ratio between the ZnO and SnO2 powders is optimized starting from equal ratios of oxide powders. The ratio of ZnO is slowly increased and XRD patterns are collected for each experiment condition. Experiment time was also extended to 30 minutes and results are recorded to prove any difference to the previous. After the optimization, the grown zinc tin oxide nanowires were used as a channel layer for a field effect transistor. The zinc tin oxide nanowire transistor exhibit a on-current of 0.12 x 10-6 A, on/off ratio of 6.09 x 102 and mobilities of 0.00152cm2/Vs. These results displayed typical output characteristics of a transistor. Although the performance produced by such zinc tin oxide nanowire is positive but not ideal, continuous research on the process and physical properties of zinc tin oxide nanowires will definitely create better results.